The lean IT field guide : a roadmap for your transformation - Orzen, Michael A.; Paider, Thomas A. (CRC Press, 2016)
This book explains how to initiate, execute, and sustain a lean IT transformation. Illuminating a clear path to lean IT, the authors provide a proven method for creating and sustaining a true lean IT workplace. This field guide not only highlights the organizational techniques of more agile and lean processes, but also the leadership work required to help management adopt these new approaches. Based on proven methods from different industries, including banking, manufacturing, insurance, food and beverage, and logistics, it details a clear model that covers all the components you need to achieve and sustain a favorable work environment and culture in support of lean IT. Filled with anecdotes and case studies from actual businesses, it includes pictures, templates, and examples that illustrate the application of the lean methods discussed. --